Assessment of the cropping cycle effects on black leaf streak severity and yield decline of plantain and plantain hybrids - Mobambo, K.N.; Gauhl, F.; Swennen, Rony L.; Pasberg-Gauhl, C. (Informa UK Limited, 1996)
Black leaf streak (BLS), an airborne fungal Black leaf streak, caused byMycosphaerella fijiensisMorelet, is a major constraint to plantain production. Owing to limitations associated with the use of chemicals in Africa, development of resistant cultivars seems to be an appropriate approach to control the cultivars. Resistance and yield performance of three plantain hybrids (TMP × 597–4, TMP × 548–4 and TMP × 548–9) were evaluated and compared with the maternal plantain ‘Obino I'Ewai’ over two cropping cycles. The three hybrids had significantly less leaf spot damage than the plantain ‘Obino I'Ewai1with and without fungicide treatment. The BLS effects on plantain yield were more severe in the ratoon crop (RC, second cycle) than in the plant crop (PC, first cycle) owing to the associated effects of the depletion of soil nutrients. Plantain yield loss from BLS was 33% in PC and 76% in RC, as calculated from the difference in yield between the fungicide‐treated and non‐treated plantain. Yield decline from PC to RC was higher in the plantain parent than in the hybrids.